Global value chains and the missing exports of the United States - Yuqing Xing (Asian Development Bank Institute (ADBI), 2017)
More and more American multinational corporations (MNCs) are outsourcing the production and assembly of their products to foreign companies. When they do so, they derive the largest share of their revenue from the intellectual property embedded in core technological innovation and brand names. However, conventional trade statistics are compiled based on the value of goods crossing national borders, as declared to customs. Generally, the value added associated with intellectual property rights and embedded in physical goods is not recorded as either export or import of any country. Hence, current trade statistics greatly underestimate US exports and substantially exaggerate its trade deficit. In this paper, we use the case of Apple, the largest American consumer products company, to illustrate the failure of conventional trade statistics to report actual US export capacity in the age of global value chains. According to our analysis of this case, if the value added of Apple intellectual property sold to foreign consumers was counted as part of US exports, total US exports in 2015 would increase by 3.4%, and its trade deficit would decrease by 7.0%. In terms of bilateral trade, the value added under examination here would raise US exports to the PRC and Japan in 2015 by 16.6% and 8.6% respectively, and lower its trade deficit with the two countries by 5.2% and 7.8% accordingly .
Keywords: F1; 330; US; exports; Apple